Sharing Our Knowledge: Feminist Collaborations across Generations - Oredein, Oluwatomisin (Journal of feminist studies in religion, 2019)
The problems of the academy are both uniquely not my own and specifically my own. No path is the same, and yet it seems like they all follow a template of certain, uncertainty, and certain uncertainty. My journey within the academy started in a happenstance manner and then yielded to a somewhat formed and vaguely structured path. I have learned thus far that chance and perpetual uncertainty is the engine that makes academia work. In offering my thoughts on sharing knowledge from my generation, I frame my experience around listening, landing, and learning. These frames helped organize the arbitrary nature of my path into academia and my current approach to making it work on this side of the scholastic fence.